Tests of commercial colour CMOS cameras for astronomical applications - Pokhvala, S.M.; Reshetnyk, V.M.; Zhilyaev, B.E. (Advances in Astronomy and Space Physics, 2013)
We present some results of testing commercial colour CMOS cameras for astronomical applications. Colour CMOS sensors allow to perform photometry in three filters simultaneously that gives a great advantage compared with monochrome CCD detectors. The Bayer BGR colour system realized in colour CMOS sensors is close to the astronomical Johnson BVR system. The basic camera characteristics: read noise (e⁻/pix), thermal noise (e⁻/pix/sec) and electronic gain (e⁻/ADU) for the commercial digital camera Canon 5D MarkIII are presented. We give the same characteristics for the scientific high performance cooled CCD camera system ALTA E47. Comparing results for tests of Canon 5D MarkIII and CCD ALTA E47 show that present-day commercial colour CMOS cameras can seriously compete with the scientific CCD cameras in deep astronomical imaging.